2013
DOI: 10.1080/13546783.2012.735622
|View full text |Cite
|
Sign up to set email alerts
|

Matching bias in syllogistic reasoning: Evidence for a dual-process account from response times and confidence ratings

Abstract: We examined matching bias in syllogistic reasoning by analysing response times, confidence ratings and individual differences. Roberts' (2005) 'negations paradigm' was used to generate conflict between the surface features of problems and the logical status of conclusions. The experiment replicated matching bias effects in conclusion evaluation (Stupple & Waterhouse, 2009), revealing increased processing times for matching/logic 'conflict problems'. Results paralleled chronometric evidence from the belief bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 56 publications
(62 reference statements)
6
43
1
Order By: Relevance
“…Three of them are explained through the matching bias [9,10], the min-heuristic [11], and the atmosphere effect [12,13]. These particular cases are concerned with syllogisms and conditionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of them are explained through the matching bias [9,10], the min-heuristic [11], and the atmosphere effect [12,13]. These particular cases are concerned with syllogisms and conditionals.…”
Section: Discussionmentioning
confidence: 99%
“…The task is to decide which card or which cards have to be known by both sides to prove that the rule is true for the given set of cards. Elaborated inferential responses are expected in the WST, but it was observed instead that subjects perform a rapid response that matches superficial features mentioned in the rule [10]. If P was mentioned in the rule, then subjects´ overall responses select the P card.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, participants often incorrectly endorse the conclusion as logically valid (Evans, Barston, & Pollard, 1983). Nonetheless, a number of studies have demonstrated that participants are able to detect the conflict between logic and belief; a finding that applies to both syllogisms (Ball, Phillips, Wade & Quayle, 2006;De Neys, Moyens, & Vansteenwegen, 2010;Stupple & Ball, 2008;Stupple, Ball, & Ellis, 2013) and conditionals (Handley, et al, 2011). According to the three-stage model (see also, De Neys, 2012), this conflict detection indicates that some or most participants must be intuitive logicians.…”
Section: Beyond Base-rate Neglectmentioning
confidence: 99%
“…Among these factors, we differentiate factors associated with the task features and factors related to individual differences. The factors related to the task may include the type of instructions provided (Evans, ; Evans, Handley, Neilens, & Over, ); the availability of sufficient time to carefully evaluate the default responses (Barrouillet, ; Evans & Frankish, ; Stupple, Ball, & Ellis, ; Stupple, Ball, Evans, & Kamal‐Smith, ; Stupple & Waterhouse, ); cueing algebraically (Hoover & Healy, ); or the change of the figures mentioned in the problem (Baron et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Low correlations between executive function measures and discrepancies among studies may be attributed to the few and heterogeneous measures used to tap executive functioning (Toplak et al ., ; Welsh, Burns, & Delfabbro, ), which highlights the need to employ a multitask approach to measure executive functioning (Stupple, Ball, & Ellis, ; Stupple, Gale, & Richmond, ; see also Miyake et al ., , or a similar account) to avoid task impurity. The influence of executive functioning on the performance for this item will be explored in Experiment 2.…”
Section: Introductionmentioning
confidence: 99%